Hubungan Self-efficacy dengan Kecemasan pada Ibu Hamil Primigravida Trimester III di Wilayah Pertanian - Dewi, Erti Ikhtiarini; Febrianty, Dyta; Kurniyawan, Enggal Hadi; Kurniawati, Dini; Deviantony, Fitrio (Jurnal Ilmiah Kesehatan, 2024)
Anxiety in pregnant women can affect the labor process due to the psychological instability that occurs. Self-efficacy is one of the factors that can reduce anxiety in pregnant women. This study has a general objective of analyzing the relationship between self-efficacy and anxiety in third trimester primigravida pregnant women in agricultural areas. This study uses correlational quantitative research with a cross-sectional survey design approach. The sample consisted of 83 respondents, selected through non-probability sampling, specifically total sampling. The research instrument for measuring the level of self-efficacy was a self-efficacy questionnaire, and the level of anxiety was measured using the Pregnancy Related Anxiety Questionnaire-Revised 2 (PRAQ-R2). Data were analyzed using Kendall's Tau-b test, and the results obtained (p-value = 0.000, p < 0.05) showed a relationship between self-efficacy and anxiety in third trimester primigravida pregnant women. Self-efficacy affects the mother's mentality during pregnancy and childbirth because high confidence in her abilities makes her more motivated to maintain her health and feel satisfaction during the childbirth process. Pregnant women with high self-efficacy may better withstand reactions that trigger anxiety because they can solve problems using their abilities and think positively about situations. The conclusion obtained is that most respondents had high levels of self-efficacy and mild anxiety levels, and there is a relationship between self-efficacy and anxiety in third trimester primigravida pregnant women. Keywords: Anxiety, Pregnant Women, Primigravida, Self-Efficacy, Third Trimester